2020
DOI: 10.4236/jep.2020.114015
|View full text |Cite
|
Sign up to set email alerts
|

Destructive and Nondestructive Determination of <sup>226</sup>Ra and <sup>228</sup>Ra in Drinking Water by Gamma Spectrometry

Abstract: The Safe Drinking Water Act (SDWA) mandates that the drinking water should be monitored for 226 Ra and 228 Ra isotopes and establishes the Maximum Contaminant Level of 185 mBq/L (5 pCi•L −1) for the sum. In addition, SDWA regulates the Detection Limit (DL) of 37.0 mBq/L (1 pCi/L) for each isotope. The purpose of this work is to develop a working method for the determination of radium isotopes in drinking water satisfying the regulatory requirements of U.S. Environmental Protection Agency by utilizing our exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Eksterni faktori su povezani sa unutrašnjim faktorima na osnovu njihovog uticaja. Istraživanje koje je korišćeno za razvoj modela je i Khanovo i Spangovo predstavljanje KFU-a u MR projektima [18]. Takođe, ko-rišćen je i Colemanov [19] zaključak da strateški lideri moraju biti u stanju da uravnoteže agilnost i doslednostm što je od značaja za organizacije koje imaju visoke hijerarhijske strukture, složene administrativne procese i procedure, rade na udaljenim geografskim lokacijama i imaju timove koje karakteriše kulturna raznolikost.…”
Section: Modelovanje Uticaja Kulture Na Liderstvo U Međunarodnim Razv...unclassified
“…Eksterni faktori su povezani sa unutrašnjim faktorima na osnovu njihovog uticaja. Istraživanje koje je korišćeno za razvoj modela je i Khanovo i Spangovo predstavljanje KFU-a u MR projektima [18]. Takođe, ko-rišćen je i Colemanov [19] zaključak da strateški lideri moraju biti u stanju da uravnoteže agilnost i doslednostm što je od značaja za organizacije koje imaju visoke hijerarhijske strukture, složene administrativne procese i procedure, rade na udaljenim geografskim lokacijama i imaju timove koje karakteriše kulturna raznolikost.…”
Section: Modelovanje Uticaja Kulture Na Liderstvo U Međunarodnim Razv...unclassified
“…The development of low-background gamma-ray spectrometer (LBGS) was originally for basic physics research such as neutrino oscillation, 0νββ decay, and dark matter search (Heusser, 1995;Povinec et al, 2004;Laubenstein et al, 2004;Aalseth et al, 2012;Armengaud et al, 2013;Khan et al, 2014) during the last two decades, however, LGBS has found several important applications such as monitoring natural radionuclides such as 226 Ra, 228 Ra (Semkow et al, 2019;Khan et al, 2020) as well as anthropogenic radionuclides such as fission products in the environment for contamination control and nonproliferation applications. The Nuclear Chemistry Laboratory (NCL) at the New York State Department of Health has been operating LBGS for over two decades (Semkow et al, 2002;Haines et al, 2011;Khan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%